Development and death of external granular layer cells in the weaver mouse cerebellum: a quantitative study - Smeyne, RJ (J Neurosci, 1989)
Previous studies have identified the cerebellar granule cell as a primary site of gene action in the weaver mutant mouse. The temporal expression of the weaver mutant granule cell phenotype has not been fully investigated. To identify early postnatal expression of the weaver mutant phenotype, we quantitated 4 parameters of cerebellar development in postnatal day 0, 2, 4, 6, and 8 +/+, wv/+, and wv/wv mice: (1) cerebellar area, (2) cells in the external granule layer (EGL), (3) number of mitotic figures in the EGL, and (4) number of pyknotic figures in the EGL. Qualitative observations suggest a generalized retardation in the development of wv/wv and wv/+ EGL cells compared with the +/+ cells. Quantitatively, the earliest detectable mutant phenotype in wv/wv and wv/+ cerebella is the increased presence of cell death in the EGL, apparent at the day of birth. Degenerating cells in the EGL, the majority of which are found in the postmitotic zone of this layer, contain abnormally clumped heterochromatin, suggestive of “nuclear” cell death. Previous hypotheses concerning the mechanism of weaver gene action have suggested that granule cells die due to their inability to migrate from the EGL. The time course, mode, and spatial organization of cell death found in the present studies lead us to suggest that an earlier event in granule cell development, such as the exit of neuroblasts from the cell cycle or axonogenesis, is affected by the weaver gene.